A model‐based framework for correcting B1+ inhomogeneity effects in magnetization transfer saturation and inhomogeneous magnetization transfer saturation maps. Issue 4 (6th May 2021) - Rowley, Christopher D.; Campbell, Jennifer S. W.; Wu, Zhe; Leppert, Ilana R.; Rudko, David A.; Pike, Gilbert Bruce; Tardif, Christine L.
Abstract : Purpose: In this work, we propose that Δ B 1 + ‐induced errors in magnetization transfer (MT) saturation (MTsat ) maps can be corrected with use of an R1 and B 1 + map and through numerical simulations of the sequence. Theory and Methods: One healthy subject was scanned at 3.0T using a partial quantitative MT protocol to estimate the relationship between observed R1 (R1, obs ) and apparent bound pool size ( M 0, a p p B ) in the brain. MTsat values were simulated for a range of B 1 +, R1, obs, and M 0, a p p B . An equation was fit to the simulated MTsat, then a linear relationship between R1, obs and M 0, a p p B was generated. These results were used to generate correction factor maps for the MTsat acquired from single‐point data. The proposed correction was compared to an empirical correction factor with different MT‐preparation schemes. Results: M 0, a p p B was highly correlated with R1, obs (r > 0.96), permitting the use of R1, obs to estimate M 0, a p p B for B 1 + correction. All B 1 + corrected MTsat maps displayed a decreased correlation with B 1 + compared to uncorrected MTsat and MTsat corrected with an empirical factor in the corpus callosum. There was good agreement between the proposed approach and the empirical correction with radiofrequency saturation at 2 kHz, with larger deviations seen when using saturation pulses further off‐resonance and in inhomogeneous (ih) MTsat maps. Conclusion: The proposed correction decreases the dependence of MTsat on B 1 + inhomogeneities. Furthermore, this flexible framework permits the use of different saturation protocols, making it useful for correcting B 1 + inhomogeneities in ihMT.